Digital platforms’ use in SMEs – A critical analysis of entrepreneurs’ behaviour - Madhukara Nayak; Pushparaj M. Nayak; Harisha G. Joshi (Cogent Economics & Finance)
Small and medium enterprises (SMEs) have greatly benefited from digital technology platforms, enabling entrepreneurs to connect directly with suppliers and buyers, fostering efficient communication and expanding market reach. These platforms equip SMEs with tools and resources to compete with larger organizations, driving innovation and growth. This study examines the role of age, gender, and education as moderators in the adoption of digital platforms by SME entrepreneurs in India. A theoretical model, grounded in existing literature, was tested using PLS-SEM with a sample of 700 startup entrepreneurs. The findings indicate that adopting digital platforms significantly impacts the antecedents of SME entrepreneurship intention, which in turn strongly influence the intention to adopt these platforms. The proposed model explains 63% of the variance in adoption intention. The study also highlights how demographic moderators shape digital adoption, offering insights into the evolving profile of SME entrepreneurs. These results provide valuable guidance for policymakers, business owners, and academics in shaping strategies to support SMEs in a rapidly digitalizing business environment. This research contributes to understanding the interplay between demographic factors and digital platform adoption, aiding stakeholders in fostering SME growth and innovation through targeted interventions.